Community College Engineering Students' Perceptions of Classroom Climate and Fundamental Engineering Skills. Issue 7 (3rd July 2019) - Stack Hankey, Maria; Burge, Penny L.; Knight, David B.; Seidel, Richard W.; Skaggs, Gary
ABSTRACT: The purpose of this study was to examine community college engineering students' perceptions of their classroom climate and how these perceptions are related to fundamental skills in engineering. The study was guided by the following research question: How are community college engineering students' perceptions of their fundamental engineering skills related to their perceptions of classroom climate? Data from a 2009 National Science Foundation sponsored project, Prototype to Production: Processes and Conditions for Preparing the Engineer of 2020 (P2P), which contains information from students in 15 pre-engineering community college programs, were examined. Measures of classroom climate and fundamental skills related to engineering were first established through an exploratory factor analysis. In order to explore differences in student perceptions by individual characteristics and by institution, hierarchical linear modeling (HLM) was used. Results indicated that for community college engineering students, a warmer perception of classroom climate was associated with a higher perception of fundamental engineering skills. At community colleges, class sizes are generally smaller, especially compared to introductory courses at universities, and may provide a warmer climate for students considering beginning their engineering degrees. Given the diversity within community colleges, these institutions may provide an important pathway for underrepresented groups in engineering.